Antipsychotic pitfalls: idiopathic intracranial hypertension and antipsychotic-induced weight gain - Namiki, Hirofumi (BMJ Case Rep, 2020)
Idiopathic intracranial hypertension (IIH) is a condition associated with poor vision and headaches that can cause disability and reduced quality of life. The onset of IIH is typically associated with sudden weight gain and obesity, which may be due to first-generation or second-generation antipsychotics. This case involved the use of quetiapine in an obese, 28-year-old woman; she gained significant weight after starting the antipsychotic and later developed headaches and blurred vision. Reducing quetiapine and administering acetazolamide significantly improved her symptoms within 4 weeks. This case reminds physicians to consider IIH as a cause of headache and vision loss in patients who have gained weight after starting or increasing quetiapine.